2020
DOI: 10.1111/aor.13818
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of patients suffering unwitnessed hypothermic cardiac arrest rewarmed with extracorporeal life support: A systematic review

Abstract: Prolonged cardiac arrest (CA) may lead to neurologic deficit in survivors. Good outcome is especially rare when CA was unwitnessed. However, accidental hypothermia is a very specific cause of CA. Our goal was to describe the outcomes of patients who suffered from unwitnessed hypothermic cardiac arrest (UHCA) supported with Extracorporeal Life Support (ECLS). We included consecutive patients’ cohorts identified by systematic literature review concerning patients suffering from UHCA and rewarmed with ECLS. Patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 31 publications
(74 reference statements)
1
19
0
6
Order By: Relevance
“…According to a recent review by Frei et al patients suffering from HCA due to rescue collapse had a survival rate of 73%, and nearly 90% of the survivors had a favorable neurological outcome ( 134 ). Moreover, Podsiadło et al in a cohort of 221 patients with witnessed HCA observed an overall survival rate of 27%, whereof 83% had no neurologic deficit ( 135 ). Of note, Pasquier et al in a univariate analysis of 237 victims of CA also found that witnessed CA was associated with better survival ( P < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…According to a recent review by Frei et al patients suffering from HCA due to rescue collapse had a survival rate of 73%, and nearly 90% of the survivors had a favorable neurological outcome ( 134 ). Moreover, Podsiadło et al in a cohort of 221 patients with witnessed HCA observed an overall survival rate of 27%, whereof 83% had no neurologic deficit ( 135 ). Of note, Pasquier et al in a univariate analysis of 237 victims of CA also found that witnessed CA was associated with better survival ( P < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Februar 2020 wurde eine PubMed-Recherche zu den Schlüsselwörtern „Lawine“ UND „Rettung“ ( n = 100) durchgeführt. Dabei wurden vier systematische Übersichtsarbeiten gefunden [ 162 165 ]. Die relevanten Publikationen aus den systematischen Übersichtsarbeiten wurden eingeschlossen und die Literatur mit Blick auf weitere Veröffentlichungen überprüft.…”
Section: Evidenz Die In Die Leitlinien Einfließtunclassified
“…Eine weitere Übersichtsarbeit zu unterkühlten Patienten, bei denen der Eintritt des Kreislaufstillstands nicht beobachtet wurde ( n = 221), fand eine Überlebensrate von 27 %; 83 % waren neurologisch unauffällig. Bemerkenswert dabei ist, dass bei 48 % der Überlebenden der erste abgeleitete Rhythmus eine Asystolie war [ 165 ]. Unterkühlte Patienten, bei denen es zu einem Kreislaufstillstand kommt, sollen ununterbrochen wiederbelebt werden, bis ein Kreislauf wieder hergestellt ist.…”
Section: Evidenz Die In Die Leitlinien Einfließtunclassified
See 1 more Smart Citation
“…Surviving prolonged burial ( ‡60 minutes) is only possible if an air pocket exists, that is, patent airway and any space in front of nose and mouth. Chances of survival with favorable outcome of an avalanche victim are higher if the buried subject rapidly cooled to <30°C and arrested only thereafter (Frei et al, 2019;Podsiadlo et al, 2021). A low core temperature reduces oxygen metabolism in the body and protects the most oxygen-dependent organs, the brain and heart, from any hypoxia-induced damage longer than in normothermia (McCullough et al, 1999).…”
Section: Introductionmentioning
confidence: 99%